The Caterpillar Way: Lessons in Leadership, Growth, and Shareholder Value (Audio Book) - Bouchard, Craig; Koch, James (McGraw-Hill, 2013)
THE NEW YORK TIMES BESTSELLER! How one tenacious company found the drive to succeed--on a global scale In the early 1980s, Caterpillar, Incorporated lost one million dollars per day for three consecutive years. Its continuing existence came into question. Today, "CAT" is the world's most profitable manufacturer of construction and mining equipment and large engines. The now legendary global company made numerous well-calculated, though risky decisions for three consecutive decades--in the process scaling to heights unimaginable to even the finest business enterprises. How did they do it? The Caterpillar Way . Senior management at CAT facilitated the authors' one-year odyssey through the hallways and intriguing history of the construction industry giant. This inspiring book takes you behind the scenes with the CEOs, executive vice presidents, managers, dealers, customers, union bosses, and Wall Street analysts who were players in Caterpillar's drive to global dominance. You'll discover: CAT's change-or-die approach to restructuring How a local firm from central Illinois became a local firm on a global basis The secret behind Caterpillar's decades-long revenue explosion How to use branding and product financing effectively What true dedication and commitment to Six Sigma really entails Why Caterpillar became the mecca for HR officers negotiating with unions The authors' prediction of CAT's stock price through 2020 The Caterpillar Way provides essential management lessons in powerful behind-the-scenes stories. You'll learn how the Caterpillar leaders responded quickly to changing markets, allocated capital efficiently throughout the firm, and nourished a cultish team spirit that wins. Innovative leaders make game-changing decisions. If any company is built to last, it's Caterpillar, Inc. With its trademark yellow trucks, cranes, machinery and engines, this home-grown manufacturer has survived more than its share of ups and downs to become the #1 industry leader of construction equipment in the world. The Caterpillar Way reveals, for the first time, the remarkable inside story, written with full access to the way CAT runs its business, from bottom to top. They blaze their own trail. This is The Caterpillar Way . PRAISE FOR THE CATERPILLAR WAY : " The Caterpillar Way is a very sophisticated analysis of one of the great organizational stories of the past 30 years. Bouchard and Koch delve into the details of leadership, risk, and culture that allowed this co...